Characterization of the components of the thioredoxin system in Bacteroides fragilis and evaluation of its activity during oxidative stress - Paunkov Ana (ANAEROBE, 2022)
Objectives: Bacteroides fragilis has a pronounced ability to survive prolonged exposure to atmospheric oxygen. The major objective of this study was to biochemically characterize the components of the thioredoxin system in B. fragilis. The nitroreductase activity of TrxR was also assayed. Methods: Components of the thioredoxin system were expressed in E. coli and used in a disulfide reductase activity assay. Activity of TrxR was measured with purified recombinant enzyme or with cell extracts after or without exposure to oxygen or hydrogen peroxide, respectively. Results: Of all six thioredoxins tested, only thioredoxins A, D, and F were reduced by recombinant TrxR and natural TrxR present in B. fragilis cell extracts. Exposure to oxygen and hydrogen peroxide increased the activity of TrxR. Further, B. fragilis TrxR acts as a nitroreductase with furazolidone or 1-Chloro-2,4dinitrobenzene as substrates but cannot reduce metronidazole. Conclusion: TrxR shows an increase in activity under the conditions of oxidative stress and exerts nitroreductase activity. (c) 2021 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).